2019
DOI: 10.1177/1038416219830419
|View full text |Cite
|
Sign up to set email alerts
|

Linking succession planning to employee performance: The mediating roles of career development and performance appraisal

Abstract: Drawing on social exchange theory, the objectives of the study were to examine how succession planning relates to employee performance and assess whether career development and performance appraisal mediate this relationship. Using survey methodology, data were collected from permanent employees at several commercial banks (N = 239; 62% male). Structural equation modeling tested the proposed model. The results suggested that succession planning had a significant, positive relationship with employee performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Job rotation is another key tool that employers use to help employees in internal mobility as well as succession planning for future organizational needs. Succession planning, a critical driver of organizational and leader restoration, generates a competitive pool of skilled people by offering uninterrupted services to enhance organizational productivity (Ali et al, 2019). To be complete and effective, succession planning templates (consisting of critical skill sets required for the leadership position, employees' current level of competency and possible future requirements) are created, continually reviewed and updated to reflect changes in the organization's operation.…”
Section: Career and Succession Planningmentioning
confidence: 99%
“…Job rotation is another key tool that employers use to help employees in internal mobility as well as succession planning for future organizational needs. Succession planning, a critical driver of organizational and leader restoration, generates a competitive pool of skilled people by offering uninterrupted services to enhance organizational productivity (Ali et al, 2019). To be complete and effective, succession planning templates (consisting of critical skill sets required for the leadership position, employees' current level of competency and possible future requirements) are created, continually reviewed and updated to reflect changes in the organization's operation.…”
Section: Career and Succession Planningmentioning
confidence: 99%
“…Moreover, Rousseau and Tijoriwala (1998) indicated that the culture within an organisation sets the normal patterns of behaviour, and this frames the psychological contract; adhering to these norms can become part of the performance commitment; whereas a psychological contract breach has an adverse impact on performance (Matthijs Bal, Chiaburu, & Jansen, 2010). A perceived unfairness in the appraisal process can result in dissatisfaction and diminished performance (Ali, Mahmood, & Mehreen, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Selecting the right successor is utmost to the firm endurance. Organizations with right person decrease problems, enhance innovation, accelerate employee morale and improve intellectual capital (Ali et al, 2019). Succession planning declines the risk of hiring an inappropriate employee for essential roles.…”
Section: Succession Planning and Employee Performancementioning
confidence: 99%
“…Friday (2019) studied the association between employee training and succession planning in ten commercial banks and found that training positively improves succession practices, which, in turn, leads to employee performance. Recently, Ali et al (2019) stated that succession planning is significantly related to employee performance, while Gordon and Overbey (2018) theoretically stated that succession planning brings worker satisfaction and superior performance. Eugene Fibuch and Van Way (2012) stated that succession planning generates the key knowledge and skills domain that link with future leaders.…”
Section: Succession Planning and Employee Performancementioning
confidence: 99%